WAYS TO REFORM HEALTH CARE FACILITIES IN UKRAINE - Базелюк, Юлія (Human Geography Journal, 2015)
Features of health care decentralization are considered in this article. Main attention paid to reasons reform realization. World experience in health care finances managing analyzed. Main role and nature of health services in functioning of health care facilities services determined. Short retrospective analysis health care reforms in Ukraine was made. Models and methods of health care decentralization in Ukraine within region analyzed. Main ways of heath care facilities financing reforms were determined.